Walkabout - Roeg, Nicolas 1928-2018; Barry, John 1933-2011 (<<The>> Criterion Collection, 2010)
"A young sister and brother are abandoned in the harsh Australian outback and must learn to cope in the natural world, without their usual comforts, in this hypnotic masterpiece from Nicolas Roeg. Along the way, they meet an Aboriginal youth on his walkabout, a rite of passage in which adolescent boys are initiated into manhood by journeying into the wilderness alone. Walkabout is a thrilling adventure as well as a provocative rumination on time and civilization." [criterion.com]
Original: Großbritannien, Australien 1971
Director-approved special edition double-DVD set features: new, restored high-definition digital transfer, made from a newly minted 35 mm interpositive and approved by director Nicolas Roeg ; audio commentary featuring Roeg and actress Jenny Agutter ; video interviews with Agutter and actor Luc Roeg ; Gulpilil: One red blood (2002), a documentary on the life and career of actor David Gulpilil ; theatrical trailer ; plus: An essay by author Paul Ryan
Bildformat 1.78:1
Keywords: Film; DVD-Video